Analisis pengaruh kompetensi, dan sertifikasi terhadap kinerja guru yang dimediasi motivasi pada guru SMK se Kabupaten Manokwari - Sugiono, Edi; Wulandari, Andini; Mandacan, Obelani (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of competence and certification on teacher performance mediated by teacher motivation at SMK in Manokwari Regency and to provide suggestions on how teacher performance should be evaluated. Competence (X1) and certification (X2) are independent variables. The dependent variable is teacher performance (Y) and the intervening variable is motivation (Z). The research approach used for this research is in accordance with quantitative research, namely interviews, observations, and surveys. The model was analyzed using SEM AMOS statistical software version 22. The survey-based data was collected from 100 respondents. This study found that competence directly has a positive and significant effect on motivation. Certification has a direct and significant negative effect on motivation. Certification competence, as well as each motivation, have a direct impact on teacher performance. directly has a positive and significant effect on teacher performance. Certification has a negative and significant effect on teacher performance through motivation.